Problematika Pembelajaran Muhadatsah Pada Siswa Kelas VIII B SMPIT Ar-Raihan Bandar Lampung - Yeni Yunita; Ahmad Hadi Setiawan; Khairil Anwar (Program Studi Pendidikan Bahasa Arab, 2023)
The purpose of this study was to find out the process of muhadatsah learning in class VIII B students of SMPIT Ar-Raihan, and the problems faced by teachers and students in muhadatsah learning. The questions in this study include